Individual and Composite Adverse Pregnancy Outcomes in a Randomized Trial on Isoniazid Preventative Therapy Among Women Living With Human Immunodeficiency Virus. (30th September 2020) - Theron, Gerhard; Montepiedra, Grace; Aaron, Lisa; McCarthy, Katie; Chakhtoura, Nahida; Jean-Philippe, Patrick; Zimmer, Bonnie; Loftis, Amy James; Chipato, Tsungai; Nematadzira, Teacler; Nyati, Mandisa; Onyango-Makumbi, Carolyne; et al.
Abstract: Background: International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) P1078, a randomized noninferiority study designed to compare the safety of starting isoniazid preventive therapy (IPT) in women living with human immunodeficiency virus (HIV) either during pregnancy or after delivery, showed that IPT during pregnancy increased the risk of composite adverse pregnancy outcomes, but not individual outcomes. Many known factors are associated with adverse pregnancy outcomes: these factors' associations and effect modifications with IPT and pregnancy outcomes were examined. Methods: Pregnant women living with HIV from 8 countries with tuberculosis incidences >60/100 000 were randomly assigned to initiate 28 weeks of IPT either during pregnancy or at 12 weeks after delivery. Using univariable and multivariable logistic regression and adjusting for factors associated with pregnancy outcomes, composite and individual adverse pregnancy outcome measures were analyzed. Results: This secondary analysis included 925 mother-infant pairs. All mothers were receiving antiretrovirals. The adjusted odds of fetal demise, preterm delivery (PTD), low birth weight (LBW), or a congenital anomaly (composite outcome 1) were 1.63 times higher among women on immediate compared to deferred IPT (95% confidence interval [CI], 1.15–2.31). The odds of fetal demise, PTD, LBW, or neonatal death within 28 days (composite outcome 2) were 1.62 times higher among women on immediate IPT (95% CI, 1.14–2.30). The odds of early neonatal death within 7 days, fetal demise, PTD, or LBW (composite outcome 3) were 1.74 times higher among women on immediate IPT (95% CI, 1.22–2.49). Conclusions: We confirmed higher risks of adverse pregnancy outcomes associated with the initiation of IPT during pregnancy, after adjusting for known risk factors for adverse pregnancy outcomes. Abstract : After adjusting for known risk factors, we compared composite and individual adverse pregnancy outcomes in women with human immunodeficiency virus initiating isoniazid preventive therapy during or after pregnancy, and found higher risks of adverse pregnancy outcomes with initiation during pregnancy.